Peran Inkubator Bisnis Perguruan Tinggi dalam Peningkatan Kinerja Usaha UKM Pangan - Rokhani Hasbullah; Memen Surahman; Ahmad Yani; Deva Primadia Almada; Elisa Nur Faizaty (Jurnal Ilmu Pertanian Indonesia, 2015)
Businesses in food processing plays an important role in the national economy. Facing the ASEAN Economic Community (AEC), the performance of the food SMEs needs to be improved in order to compete in the ASEAN region. One of the institutions that play a role in nurturing the business SMEs is Business Incubators. This study aimed to assess the performance of University Business Incubators in nurturing the incubator tenants and to assess the effect of incubation program on the performance of Food SMEs tenants. Research was conducted at several Business Incubators belong to universities by interviewing managers and tenants of the Business Incubators that have focus on the food processing sector. Data were analyzed using balanced scorecard (BSC). The results showed that most of the University Business Incubators have sufficient performances (75) and only a small portion performs well (17) and excellent (8). Business Incubators in general have several limitations such as limitations in process, quality, and facility in incubation program, low efficiency and financial independence. Business Incubators have contributed in improving the business performance of the tenants by increasing the number of labor, the turnover, the market region, and the access to financial sources.